PENERAPAN IPTEKS BAGI KELOMPOK TANI TERNAK SAPI-KELAPA DI DESA SAWANGAN - Pudjihastuti, Endang (Universitas Sam Ratulangi, 2016)
THE APPLICATION OF SCIENCE AND TECHNOLOGY FOR BEEF-CATTLE AND COCONUT FARMER GROUPS IN SAWANGAN VILLAGE. Agriculture and livestock development are beneficial and mutually depending each other, so that integrated farming systems provide great benefits for both aspect. But there are some problem for this: Two beef-cattle farmer groups â€œHabel Iâ€ and â€œHabel IIâ€ at Sawangan Village, District Airmadidi, North Minahasa regency do not have any understanding and knowledge about proper cattle-farming development. Based on this, it has made â€‹â€‹the empowerment of members of the group through the application of science and technology with counseling and training methods. Principally, beef cattle business success is determined by three interrelated elements, e.g. seeds, feed and management. Beef-cattle farmer groups â€œHabel Iâ€ and â€œHabel IIâ€ integrates cattle-farming with coconut plantations simultaneously. Utilization of field under coconut trees to forage also serves as a cover crop. Members of the farmer group responded well to the application of science and technology activities through counseling and training , it can be seen from the availability of dwarf elephant grass in coconut plantations covering an area of 0.5 Ha . Other products produced in the form of silage and compost as well as the implementation of an assisted insemination ( 5 cows) . The application of science and technology through IbM activities can be resumed if thereâ€™s any assistance from the universities. Â Keywords: Cattle, coconut, science technology, farmer groups